ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PADA INDUSTRI MANUFAKTUR BESAR DAN SEDANG DI PROVINSI SULAWESI SELATAN - Susi; Hasbiullah, Hasbiullah; Asrahmaulyana, Asrahmaulyana (LPPM - STIE SAKTI ALAM KERINCI, 2026)
This study aims to analyze the effect of the number of business units, Provincial Minimum Wage (UMP), and technology on labor absorption with production value as an intervening variable in large and medium manufacturing industries in South Sulawesi Province. This research uses a quantitative approach with path analysis techniques assisted by SPSS software. The data used are secondary time series data obtained from official publications of the Central Bureau of Statistics (BPS) of South Sulawesi for the period 2017–2025. The variables analyzed include the number of business units, UMP, technology, production value, and labor absorption. The results show that the number of business units has a positive and significant effect on labor absorption. Conversely, the Provincial Minimum Wage has a negative and significant effect on labor absorption. Meanwhile, technology does not have a significant effect on labor absorption. In addition, production value is proven to have a positive and significant effect on labor absorption. As an intervening variable, production value is not able to mediate the effect of the number of business units and technology on labor absorption, but it is able to mediate the effect of the Provincial Minimum Wage on labor absorption. These findings indicate that increasing industrial production activities plays an important role in encouraging labor absorption in the manufacturing industry sector in South Sulawesi Province.